Development of An Online Metaverse Lesson Using Self-Directed Learning to Enhance Problem-Solving Ability - Wadtan, Riana (วารสารการวิจัยการบริหารการพัฒนา, 2025)
This study aimed to: (1) develop an online Metaverse lesson using self-directed learning to enhance problem-solving ability, (2) compare pre-test and post-test learning achievement, (3) compare problem-solving ability before and after learning, and (4) assess students' satisfaction. The target group comprised 49 undergraduate students from Chanthaburi College of Dramatic Arts enrolled in the course 300-11003 Life Skills in Higher Education in the Digital Age during the first semester of the 2024 academic year. A one-group pretest-posttest experimental design was employed. Research instruments included: (1) structured interviews, (2) lesson plans, (3) an online Metaverse lesson using self-directed learning, (4) a learning achievement test, (5) a problem-solving ability assessment, and (6) a student satisfaction questionnaire. The findings revealed that: (1) the quality of the online Metaverse lesson was rated as excellent by experts ( = 4.52, SD = 0.55), (2) students' problem-solving ability significantly improved after learning ( = 21.22, SD = 1.92) compared to before learning ( = 13.51, SD = 2.39), (3) students' post-learning achievement ( = 33.47, SD = 3.37) was significantly higher than pre-learning achievement ( = 17.27, SD = 3.21), and (4) students reported a high level of satisfaction with the learning module ( = 4.59, SD = 0.48). These findings suggest that an online Metaverse lesson using self-directed learning is an effective approach to enhancing both learning achievement and problem-solving skills. Additionally, it promotes positive learning experiences, fostering deeper learning engagement. This research provides a foundation for the future development of technology-driven instructional media to improve education for diverse learners.